E-book limitation with library portable document format java script for accessing digital library - Harliyus Agustian; Agung Nugraha (Compiler, 2021)
The function of the Adisutjipto-Aerospace Institute of Technology (ITDA) library is to provide borrowing and reimbursement services for books insured by members of the library. The books which increase in number each year occupy a lot of space in the library, it is therefore necessary to study it so that the form of this book is no longer physical but digital or paperless to be able to be stored on a server computer. This form of library is known as a digital library or e-library. The electronic library is a modern library as a place which provides a source of educational information with more convenience and security. The flow in the application is not very different from the flow in the manual library. Security becomes an important part of an application, by limiting network access, accessing PDF documents and implementing PDF Viewer using the PDF.js library by rendering PDF documents on a canvas capable of blocking illegal downloads. Based on the test results, the electronic library application can work properly. The speed of opening a PDF document is influenced by the speed of the server, the content contained in the PDF and the size of the PDF file.